Overvejelser angående det leksikografiske grundlag for en elektronisk bilingval regnskabsordbog - Nielsen, Sandro (LexicoNordica, 2002)
This paper describes some selected aspects of the pre-conceptual work in connection with an Internet-based Danish-English dictionary treating the field of accounting. The emphasis is on text-dependent and text-independent functions related to the intended user group, as this relationship is crucial in the design and preparation of this type of dictionary. In contrast to existing dictionaries within this field, this is a syntagmatic dictionary with many types of information that are designed to help the user produce and translate texts. The dictionary articles will contain such types of information as grammatical information, definitions, equivalents, pronunciation, collocations, phrases, cross-references and Internet links.